PENGARUH KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN PT. JAWA POS MEDIA TELEVISI (JTV) SURABAYA - SISWANTORO, BAMBANG (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2014)
ABSTRACTThis research was conducted to determine how the effects of compensation on employee performance PT. Jawa Pos Media Televisi (JTV) Surabaya. This research is an associative type of research is to determine the relationship between two variables is causal (cause-effect). The approach used is so much required quantitative approach using a number, ranging from data collection, interpretation of data as well as the appearance of the result. The population in this research were all employees of PT. Jawa Pos Media Televisi (JTV) Surabaya consisting of 154 employees. Sampling Slovin formula so obtained 61 employees. Step data analysis techniques using simple regression analysis t test and also test the classical assumption of normality test and test heterocedastisity. The result showed the coefficient of determination indicates that the performance is affected by the variable compensation of 57.8% while the remaining 42.2% is influenced by other variables not included in this research. Which means it can be concluded that there is a significant effect of the variable compensation to variable employee performance PT. Jawa Pos Media Televisi (JTV) Surabaya.Keywords: Compensation, Employee Job Performance